Lectures in medical education today. To be or not to be… Retrospective view - Dyagovets K.I.; Tverdokhlib I.V. (Морфологія, 2016)
Background. We live in an era of powerful technical progress. Modern education system has not always kept pace with this development. We’re dealing with new students and their new information request. So, our lecture’s system and theoretical material delivery needs to be reformed. Objective. Determine the need for and delivery of histology lecture material for graduate students of the last decade from the SI «DMA Ministry of health of Ukraine». Methods. 60th graduate student’s views were collected and partially processed in the application «Pool app» of Facebook. Within the application were collected and counted the votes, their percentage ratio in the selection and gender of participants. Results and conclusion. We analyzed results of the interview by the percentage ratio in the selection. It was established that histology lectures need for the allocation of primary from the secondary to present information situation today. During this experiment was observed the division of participants into age groups for the three proposed categories views of the form of lecture delivery. The oldest age group (2006-2008 graduate’s year (g.y.)) selected traditionally histology lectures, the middle group (2009-2011 g.y.) favoured of the additional histology lectures for postgraduate categories in consulting form and the younger group (2012-2016 g.y.) picked on the system of webinars and audio lectures replace to usual. Summing we saw the evolution of graduate student’s mind towards rationalizing delivery of theoretical material with the use of modern information resources. Citation: Dyagovets KI, Tverdokhlib IV. [Lectures in medical education today. To be or not to be… Retrospective view]. Morphologia. 2016;10(2):99-105. Ukrainian.